Audit Sistem Informasi Pelayanan Bpjs Kesehatan Menggunakan Framework Cobit 5.0 - Nurhafieza Nurhafieza; Dila Aulia Putri; Nurfadillah Nurfadillah; Evi Vusvitasari (Universitas Katolik Widya Karya Malang, 2024)
BPJS Health is a legal entity formed to administer the health insurance program with the aim of protecting the entire community with affordable premiums and providing wider service coverage for the entire community. BPJS health services focus on first level health services (FKTP/first level health facilities). Due to the sensitive nature of health information stored and managed by BPJS Health, it is important to ensure that the information systems used are safe from cyber attacks and data leaks. The stages of a BPJS Health service audit are determining audit objectives, identifying services using the framework, capability level analysis, testing controls and evidence at the capability level, verifying results, and compiling audit results reports and recommendations. Audits carried out for services that focus on Process Domains DSS01 and DSS02. The measurement result is 2.5 because the value rounding index means the results are at level 3 (established process), that is, currently the processes in each process domain have been identified and standardized well so that the library service system is stable for implementation, while the expected level is at level 4 so there is a gap of 1.5. To be able to overcome the existing gap, a recommendation was made, namely to maximize the alignment of Company Operational Standards (SOP) with applicable policies.